Analysis of Factors Affecting Anxiety on Midwife Officers At Bungah Community Health Center During Covid-19 Pandemic - Achmad Sakhowi Al Awwarij; Indriati Paskarini; Yustinus Denny Ardyanto Wahyudiono; Muhammad Nukhan (Publikasi Indonesia, 2022)
Introduction. Midwives must continue to carry out their duties in checking health of mothers and children and childbirth during COVID-19 pandemic, This condition makes them feel anxious. prevalence of anxiety for health workers during a pandemic is 44.7%. This study aims to analyze influence of factors that influence anxiety in midwives at Bungah Health Center during a covid-19 pandemic. Method. type of research is an analytic study with a cross-sectional approach. sample in this study were all midwives at Bungah Health Center as much as 32 respondents. variables in this study were age, education, knowledge, availability of PPE, and anxiety which were measured using Hamilton Anxiety Range Scale (HARS) questionnaire, and data were analyzed using binary logistic regression statistical tests. Result. results showed that 50% of midwives experienced anxiety. 68.75% of midwives are >35 years old. 84.37% of midwives have 3-years diploma, 59.37% of midwives have good knowledge, and 68.75% of midwives stated that PPE is complete. results of statistical tests showed that there was an influence between age and knowledge on anxiety of midwives with OR values 1.877 and 0.306, while education and availability of PPE did not have a significant effect on midwives anxiety. Conclusion. Age and knowledge have an effect on anxiety in midwives at Bungah Health Center, midwives with age> 35 years are at risk of experiencing anxiety by 1.87 times greater than with age <35 years, and midwives with good knowledge are at risk of experiencing anxiety by 0.3 times greater than with poor knowledge.